First experiences of ultrasound vector flow imaging at the femoropopliteal artery in peripheral arterial disease - Shchetynska-Marinova, Tetyana; Gerdes, Laurin; Hohneck, Anna; Winter, Laura; Amendt, Klaus; Schwenke, Kay; Gerken, Andreas; Du, Yigang; Dürschmied, Daniel; Sigl, Martin (Vasa, 2023)
Background: The femoropopliteal artery (FPA) plays a central role in diagnosing and treating peripheral arterial disease (PAD). FPA lesions are the most frequent cause of intermittent claudication, and no other artery of the lower extremities is recanalised more frequently. Generally, ultrasound is the primary imaging tool in PAD, particularly FPA. With the development of high-frame-rate ultrasound technology in addition to traditional ultrasound modes, vector flow imaging (VFI) has provided deeper haemodynamic insights when used in the carotid artery. Here, we report the use of VFI at the FPA level in routine PAD examinations. Patients and methods: In this single-centre prospective study, we evaluated consecutive patients with PAD using B-mode imaging, colour Doppler, pulsed wave Doppler (PW) and vector flow. Hemodynamic parameters at predefined locations at the carotid artery and FPA were compared. Results: Qualitatively adequate VFI at all sites was possible in 76% of the patients with PAD. With decreasing volume flow from the common carotid artery to the internal carotid artery and from the common femoral artery via the superficial femoral artery to the popliteal artery, the correlation between VFI- and PW-derived-volume flow was high at every site. Based on different techniques, the VFI-derived values were significantly lower than the PW-derived values. The mean wall shear stress was significantly lower at all femoropopliteal sites than at the carotid sites, whereas the oscillatory shear index at the femoral site was higher than that at the carotid sites rather than at the popliteal location. Conclusions: Our findings suggest that vector flow data acquisition in the FPA is feasible in most patients with PAD. Therefore, with knowledge of the method and its limitations, VFI provides haemodynamic information beyond traditional ultrasound techniques and is a promising new tool for flow analysis in PAD.